Methodological subcompetence of the future teacher of French for the improvement of professionally oriented orthographic competence - Н. В. Майєр (Іноземні мови, 2015)
The article describes the methodological subcompetency of the future teacher of French for the improvement of professionally oriented orthographic competence. Based on the characteristics of professionally oriented orthographic competence of future teachers of French, methodological knowledge, skills and abilities, that should be mastered by the students for the effective implementation of professional-methodical activity in the formation of the specified competencies, are defined.